The effects of the gut bacterial product, gassericin A, on obesity in mice - Valeh Mahdavi; Hamid Reza Kazerani; Fereidoun Taghizad; Hedyeh Balaei (Lipids in Health and Disease)
Abstract Background Obesity can arise from various physiological disorders. This research examined the impacts of the bacteriocin, gassericin A, which is generated by certain gut bacteria, using an in vivo model of obesity. Methods Fifty Swiss NIH mice were randomly assigned to five different groups. One group was given a standard diet, while the remaining groups were fed a diet high in fat and sugar. The test groups received gassericin A at doses of 0.75, 1.5, or 3 mIU/kg through intraperitoneal injection, daily for 10 weeks. Body weight, fasting blood sugar, serum lipid profile, and hepatic function indicators were then assessed. Additionally, the blood profile, markers of oxidative stress, and expression levels of specific genes associated with obesity, Zfp423, and Fabp4, were evaluated in abdominal adipose tissue. Results A high-calorie diet negatively impacted abdominal fat, serum cholesterol, LDL, and hepatic enzymes. However, gassericin A significantly improved these effects, despite increasing weight gain and abdominal fat. Furthermore, it improved redox status, downregulated the Zfp423 gene, and enhanced the expression of the Fabp4 gene. Finally, the bacteriocin caused thrombocytopenia and mild decreases in erythrocytes, hematocrit, and hemoglobin levels. Conclusions These results suggest that, despite causing weight gain, gassericin A may improve obesity-related complications.